The badger knight - Erskine, Kathryn (New York : Scholastic Press, 2014)
In England in 1346 Adrian has three problems: he is small for his twelve years, he is an albino, so people are suspicious of him, and his father wants him to be a scribe, while he wants to be an archer--but when he runs away to join his friend in the fight against the invading Scots, he learns that war can be a lot more complicated then he imagined.
Keywords: Archers -- England -- Juvenile fiction; Albinos and albinism -- England -- Juvenile fiction; Friendship -- Juvenile fiction; Adventure stories; Great Britain -- History -- Edward III, 1327-1377 -- Juvenile fiction; Archers -- Fiction; Runaways -- Fiction; Albinos and albinism -- Fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Great Britain -- History -- Edward III, 1327-1377 -- Fiction